Budaya Organisasi dan Kualitas Studi Layanan di IAIN Sultan Amai Gorontalo - Abdurrahman Mala; Munirah Munirah (Al-Ulum, 2019)
This article mainly aims to find the right model for improving service quality and user satisfaction of State Islamic of Religious Higher Education Institutions (Pendidikan Tinggi Keaagamaan Islam Negeri - PTKIN) by involving the organizational culture of Service Quality. This study purposefully contributes to the development of the field of education management, especially those related to the causality model of organizational culture. The results showed that there was a positive direct effect on Organizational Culture and Service Quality on User Satisfaction of Islamic Higher Education Institutions IAIN Sultan Amai Gorontalo. The results of this study are in line with the theory put forward by Philip Henslowe which shows that the impression obtained from the level of knowledge and understanding of facts regarding people, products or situations) is largely determined by the culture of people producing goods and services, maintaining service quality and ensuring the fulfillment of user expectations.